2013
DOI: 10.1007/s10195-013-0246-y
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of displaced intra-articular calcaneal fractures: is bone grafting necessary?

Abstract: BackgroundThe aim of this retrospective study was to determine the need for bone grafting in the surgical treatment of displaced intra-articular calcaneal fractures. We reviewed 390 cases of displaced intra-articular calcaneal fractures treated with plate osteosynthesis with or without autologous iliac bone grafting, and compared outcomes and complications related to fracture stabilization.Materials and methodsThree hundred ninety patients with displaced intra-articular calcaneal fractures that were treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 30 publications
0
31
1
1
Order By: Relevance
“…Orthopedic surgeons who insist on bone grafting believe it will stimulate fracture healing, leading to early full weightbearing, preventing posttraumatic arthritis, and increasing mechanical strength, and, thus, helping to prevent significant late collapse (13). Those who do not prefer bone grafting have suggested that internal fixation can adequately support the articular surface and that autografting could the infection rate, blood loss, postoperative pain, donor site morbidity, and complications (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Orthopedic surgeons who insist on bone grafting believe it will stimulate fracture healing, leading to early full weightbearing, preventing posttraumatic arthritis, and increasing mechanical strength, and, thus, helping to prevent significant late collapse (13). Those who do not prefer bone grafting have suggested that internal fixation can adequately support the articular surface and that autografting could the infection rate, blood loss, postoperative pain, donor site morbidity, and complications (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Worse [13] and better [15] outcomes have reported in other studies. A systematic review of literature comparing outcome of treatment of DIACF with and without bone grafting, displayed similar results for both methods [17], but after separating by reported score, patients with bone grafting had lower mean AOFAS score but a higher mean Creighton score.…”
Section: Discussionmentioning
confidence: 58%
“…Therefore, ORIF is getting method of interest for treatment of DIACF. Although the use of bone grafting in management of DIACF have an old history in medical practice, its usefulness is not still clear [13]. Rate of definite and occasionally use of bone graft in ORIF has been reported to be 20% and 42% in nationwide study in Netherlands, respectively [14].…”
Section: Discussionmentioning
confidence: 99%
“…Singh & Vinay evaluated over 300 patients with calcaneal fractures fixed with a plate, and compared those who were grafted, and those who weren't [17]. Those grafted had better restoration of Bohler's angle both immediately and after 2 years, and were able to bear weight earlier.…”
Section: Discussionmentioning
confidence: 99%